Autoantibodies against type I IFNs in patients with life-threatening COVID-19. - Bastard, Paul; Rosen, Lindsey B; Zhang, Qian; Michailidis, Eleftherios; Hoffmann, Hans-Heinrich; Zhang, Yu; Dorgham, Karim; Philippot, Quentin; Rosain, Jérémie; Béziat, Vivien; Manry, Jeremy; Shaw, Elana; et al. (Science, 2020)
Interindividual clinical variability in the course of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is vast. We report that at least 101 of 987 patients with life-threatening coronavirus disease 2019 (COVID-19) pneumonia had neutralizing immunoglobulin G (IgG) autoantibodies (auto-Abs) against interferon-ω (IFN-ω) (13 patients), against the 13 types of IFN-α (36), or against both (52) at the onset of critical disease; a few also had auto-Abs against the other three type I IFNs. The auto-Abs neutralize the ability of the corresponding type I IFNs to block SARS-CoV-2 infection in vitro. These auto-Abs were not found in 663 individuals with asymptomatic or mild SARS-CoV-2 infection and were present in only 4 of 1227 healthy individuals. Patients with auto-Abs were aged 25 to 87 years and 95 of the 101 were men. A B cell autoimmune phenocopy of inborn errors of type I IFN immunity accounts for life-threatening COVID-19 pneumonia in at least 2.6% of women and 12.5% of men.
Keywords: Adult; Aged; Aged, 80 and over; Antibodies, Neutralizing; Asymptomatic Infections; Autoantibodies; Betacoronavirus; Case-Control Studies; Coronavirus Infections; COVID-19; Critical Illness; Female; Humans; Immunoglobulin G; Interferon alpha-2; Interferon Type I; Male; Middle Aged; Pandemics; Pneumonia, Viral; SARS-CoV-2

Inborn errors of type I IFN immunity in patients with life-threatening COVID-19. - Zhang, Qian; Bastard, Paul; Liu, Zhiyong; Le Pen, Jérémie; Moncada-Velez, Marcela; Chen, Jie; Ogishi, Masato; Sabli, Ira K D; Hodeib, Stephanie; Korol, Cecilia; Rosain, Jérémie; Bilguvar, Kaya; et al. (Science, 2020)
Clinical outcome upon infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) ranges from silent infection to lethal coronavirus disease 2019 (COVID-19). We have found an enrichment in rare variants predicted to be loss-of-function (LOF) at the 13 human loci known to govern Toll-like receptor 3 (TLR3)- and interferon regulatory factor 7 (IRF7)-dependent type I interferon (IFN) immunity to influenza virus in 659 patients with life-threatening COVID-19 pneumonia relative to 534 subjects with asymptomatic or benign infection. By testing these and other rare variants at these 13 loci, we experimentally defined LOF variants underlying autosomal-recessive or autosomal-dominant deficiencies in 23 patients (3.5%) 17 to 77 years of age. We show that human fibroblasts with mutations affecting this circuit are vulnerable to SARS-CoV-2. Inborn errors of TLR3- and IRF7-dependent type I IFN immunity can underlie life-threatening COVID-19 pneumonia in patients with no prior severe infection.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alleles; Asymptomatic Infections; Betacoronavirus; Child; Child, Preschool; Coronavirus Infections; COVID-19; Female; Genetic Loci; Genetic Predisposition to Disease; Humans; Infant; Interferon Regulatory Factor-7; Interferon Type I; Loss of Function Mutation; Male; Middle Aged; Pandemics; Pneumonia, Viral; Receptor, Interferon alpha-beta; SARS-CoV-2; Toll-Like Receptor 3; Young Adult

Nasal Nitric Oxide in Primary Immunodeficiency and Primary Ciliary Dyskinesia: Helping to Distinguish Between Clinically Similar Diseases. - Zysman-Colman, Zofia N; Kaspy, Kimberley R; Alizadehfar, Reza; Nykamp, Keith R; Zariwala, Maimoona A; Knowles, Michael R; Vinh, Donald C; Shapiro, Adam J (J Clin Immunol, 2019)
PURPOSE: Primary ciliary dyskinesia (PCD) is a rare disorder of the mucociliary clearance leading to recurrent upper and lower respiratory tract infections. PCD is difficult to clinically distinguish from other entities leading to recurrent oto-sino-pulmonary infections, including primary immunodeficiency (PID). Nasal nitric oxide (nNO) is a sensitive and specific diagnostic test for PCD, but it has not been thoroughly examined in PID. Past publications have suggested an overlap in nNO levels among subjects with PCD and PID. We sought to determine if nNO measurements among patients diagnosed with PID would fall significantly above the established PCD diagnostic cutoff value of 77 nL/min. METHODS: Children > 5 years old and adults with definitive PID or PCD diagnoses were recruited from outpatient subspecialty clinics. Participants underwent nNO testing by standardized protocol using a chemiluminescence analyzer and completed a questionnaire concerning their chronic oto-sino-pulmonary symptoms, including key clinical criteria specific to diagnosed PCD (neonatal respiratory distress at term birth, year-round cough or nasal congestion starting before 6 months of age, any organ laterality defect). RESULTS: Participants included 32 patients with PID, 27 patients with PCD, and 19 healthy controls. Median nNO was 228.9.1 nL/min in the PID group, 19.7 nL/min in the PCD group, and 269.4 in the healthy controls (p < 0.0001). Subjects with PCD were significantly more likely to report key clinical criteria specific to PCD, but approximately 25% of PID subjects also reported at least 1 of these key clinical criteria (mainly year-round cough or nasal congestion). CONCLUSIONS: While key clinical criteria associated with PCD often overlap with the symptoms reported in PID, nNO measurement by chemiluminescence technology allows for effective discrimination between PID and PCD.